Philippines Economic Update, April 2017 - World Bank (World Bank, Washington, DC, 2017)
The Philippine economy remained resilient to global headwinds in 2016. While a slower-than-expected global recovery weakened net exports, surging domestic demands pushed the annual GDP growth rate to 6.8 percent, year-on-year. Investment drove economy-wide growth for the first time since 2013, as the government's expansionary fiscal-policy stance helped capital formation to expand by 20.8 percent year-on-year led by the construction sector. Consumption growth remained strong at a rate of 6.9 percent year-on-year, as accommodative monetary policies kept interest rates low, supporting a double-digit expansion in consumer lending. Meanwhile, low inflation at 1.8 percent boosted households' purchasing power, while a steady increase in remittance inflows accelerated the growth of household consumption. Overall, 2016 saw a marked rise in consumer confidence, reflecting a healthy job market and effective social protection programs.